Conflict between explicit and tacit public service bargains in UK executive agencies - Elston, T (Wiley, 2016)
Public service bargains (PSBs) define rewards, competencies, and loyalties for civil servants. They involve both explicit and tacit agreements with politicians. The article suggests that these two kinds of bargain may not be closely coordinated with one another, and can become “loosely coupled,” operating and evolving with relative independence. This is particularly likely when there is conflict between rational‐actor preferences and institutional expectations about political‐administrative behavior. Such a trade‐off can be managed by “decoupling” the explicit and tacit PSB, so that they operate differently in public and in private. Loose coupling results in inconsistent PSBs that are resistant to change, whereas decoupling highlights the compliance costs that actors face when securing cultural legitimacy for their bargains. These arguments are illustrated by the long‐term development of “Next Steps” agencies in the United Kingdom, where a marked disjuncture has emerged between the stated and practiced PSB.